2012
DOI: 10.1007/s00128-012-0640-9
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticides and Polychlorinated Biphenyls in Various Tissues of Waterbirds in Nalabana Bird Sanctuary, Chilika Lake, Orissa, India

Abstract: In order to understand whether organochlorine pesticides and polychlorinated biphenyls (PCBs) are responsible for the mortality of waterbirds in Nalaban bird sanctuary in Chilika Lake, the current investigation was carried out in tissues of 11 individuals comprising 7 species of birds. One or more residues were detected in all the tissues of birds analysed. Concentration of ∑HCH, ∑DDT, and ∑PCBs were ranged from below detectable level (BDL)-811 ng/g, BDL-1,987 ng/g and BDL-1,027 ng/g respectively. PCBs levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 11 publications
2
2
2
Order By: Relevance
“…This bird species often occurs close to human habitation where DDT is sprayed for malaria control in addition to sewage ponds and agricultural areas, and is scavenger, eats everything what it gets (Table 1). In agreement with other studies (Tanabe et al, 1998;Chen et al, 2009;Dhananjayan, 2012), p,p′DDE was the most abundant isomer and had significantly high burden in all samples studied in the lake Ziway food web (Table SI-1). It accounted for 87% on average (from 76 to 96%), followed by p,p′DDD (7% on average) in bird species (Fig.…”
Section: Ddtssupporting
confidence: 91%
See 2 more Smart Citations
“…This bird species often occurs close to human habitation where DDT is sprayed for malaria control in addition to sewage ponds and agricultural areas, and is scavenger, eats everything what it gets (Table 1). In agreement with other studies (Tanabe et al, 1998;Chen et al, 2009;Dhananjayan, 2012), p,p′DDE was the most abundant isomer and had significantly high burden in all samples studied in the lake Ziway food web (Table SI-1). It accounted for 87% on average (from 76 to 96%), followed by p,p′DDD (7% on average) in bird species (Fig.…”
Section: Ddtssupporting
confidence: 91%
“…On the other hand the levels of CHLs in hamerkop, African sacred ibis and marabou stork were uniformly low, indicating minimal exposure of CHLs to these birds. HPTs levels in muscle in our study are comparable with concentrations reported in the muscle of various bird species from northern China (non-quantifiable to 0.22 µg/g lw) (Chen et al, 2009), but lower than those in birds from India (1.1 to 91 ng/g ww) (Dhananjayan, 2012) (Table 3). HCB levels ranged from ND to 0.042 µg/g lw was by far lower than the concentration levels reported from Belgium and Green land (Jaspers et al 2006; (Table 3).…”
Section: Comparison With Other Areassupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, concentrations of all OCPs detected in the present study are lower than those reported previously in the tissues of birds in the Boraphet wetland 30 . Additionally ΣDDT concentrations were lower than those reported in some waterbird species from Orissa, India; e.g., Eurasian Spoonbill, Northern Shoveler, and Ruff 31 . The decline in OCP contamination in the Boraphet wetland may be due to the increased of restrictions on nearby OCP agricultural use.…”
Section: Discussioncontrasting
confidence: 65%
“…The significantly higher esterase activity in sera of the exposed subjects compared to the reference subjects observed in the present study was not anticipated because studies analyzing esterase activity following exposure to pesticides mainly show reduced activity [ 56 ]. However, an opposite response may be produced following long-term as opposed to acute exposure [ 57 ].…”
Section: Discussionmentioning
confidence: 75%